PENDAMPINGAN PENGELOLAAN POSDAYA AL-BAROKAH DALAM PENGEMBANGAN KEWIRAUSAHAAN MASYARAKAT DESA SEKAR WANGI KECAMATAN RAWAMERTA KAB. KARAWANG - Tika Santika; Dadan Ahmad Fadili; Ratna Sari Dewi (IKIP SILIWANGI, 2021)
The purpose of community service activity is to provide assistance to the managers of Posdaya Al-Barokah in developing entrepreneurship. Posdaya is a forum for friendship, advocacy, communication, information, education, and at the same time it can be developed into a coordinating forum for activities to strengthen family functions in an integrated manner. Posdaya Al-Barokah is engaged in family/community empowerment with fields including education, health, economy, and the environment. There are many natural resources available in the village, but the level of human resources is not yet optimal, so that people's creativity is still minimal in developing entrepreneurial innovation. The limited of community in terms supporting activities and the lack of motivation in the Posdaya activities themselves are visible problems to implement immediately. With these objectives and backgrounds, the implementation of assistance activities for the Posdaya Al-Barokah Manager in Community Entrepreneurship Development is carried out based on the mentoring method in community empowerment; (1) Dialogical stage with adult education approach and (2) Stage of Al-Barokah Posdaya management assistance in community entrepreneurship development in Sekarwangi Village, Rawamerta District, Karawang Regency. The results obtained from this activity are the management and entrepreneurship in Posdaya Al-Barokah.